The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1186/s12906-022-03647-5
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg-1 prevents elevated cytosolic Ca2+ via store-operated Ca2+ entry in high-glucose–stimulated vascular endothelial and smooth muscle cells

Abstract: Background Ginsenoside Rg-1 (Rg-1), a triterpenoid saponin abundantly present in Panax ginseng, is a type of naturally occurring steroid with known anti-diabetic and anti-inflammatory effects. In this study, we sought to confirm the effects and mechanisms of action of Rg-1 on store-operated Ca2+ entry (SOCE) in human vascular endothelial cell line (EA) and murine aortic vascular smooth muscle cell line (MOVAS) cells exposed to high glucose. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…However, few studies are available above the effect of DM on the activity of these Ca 2+clearing mechanisms VSMCs. In A7r5 cells, hyperglycemia was reported to induce a reduction in SERCA expression and activity (Searls et al, 2010;Tong et al, 2010) and an increase in PMCA and NCX activity (Han et al, 2022). However, our data showing that the decay phase of the initial increase in [Ca 2+ ] i evoked by ATP is accelerated in OZDF rat aortic VSMCs suggests that T2DM increases the activity of the Ca 2+ -clearing machinery.…”
Section: T2dm Shortens the Early Phase Of The Decay And Increases The...contrasting
confidence: 54%
“…However, few studies are available above the effect of DM on the activity of these Ca 2+clearing mechanisms VSMCs. In A7r5 cells, hyperglycemia was reported to induce a reduction in SERCA expression and activity (Searls et al, 2010;Tong et al, 2010) and an increase in PMCA and NCX activity (Han et al, 2022). However, our data showing that the decay phase of the initial increase in [Ca 2+ ] i evoked by ATP is accelerated in OZDF rat aortic VSMCs suggests that T2DM increases the activity of the Ca 2+ -clearing machinery.…”
Section: T2dm Shortens the Early Phase Of The Decay And Increases The...contrasting
confidence: 54%
“…The hyperpolarization of mitochondria in mouse vascular smooth muscle cells treated with HG was found to inhibit myosin light chain phosphatase, resulting in vascular smooth muscle contraction [ 24 ]. The exposure of murine aortic vascular smooth muscle cells to 30 mM glucose for 48 h was found to increase intracellular Ca 2+ levels through SOCE [ 25 ]. Because acute pancreatitis is frequently accompanied by ED [ 2 ] and hyperglycemia [ 26 ], intracellular Ca 2+ concentrations may be increased in the vascular smooth muscle cells of patients with acute pancreatitis, resulting in vascular hypercontraction.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with Rb 1 was found to inhibit Ca 2+ increase through SOCE in pulmonary arterial smooth muscle cells [ 20 ]. Moreover, Rb 1 significantly inhibited Ca 2+ influx through SOCE only in vascular smooth muscle cells, but not in vascular endothelial cells, exposed to 30 mM glucose for 48 h [ 25 ]. In agreement with these findings, the present study found that Rb 1 did not affect the agonist-induced vasoconstriction in aortas with HG and intact endothelium.…”
Section: Discussionmentioning
confidence: 99%